Financial Resilience: Strategies for Building a Strong Money Foundation - Apriyanti, Nike; Harisriwijayanti, Harisriwijayanti; Bella, Shinta (Coopetition : Jurnal Ilmiah Manajemen, 2024)
ABSTRACT This study investigates the dynamics of financial resilience among customers of Bank Syariah Indonesia, focusing on the roles of financial planning, saving behavior, and financial literacy. Using a quantitative approach with a sample of 80 bank customers selected via random sampling, the research employs SmartPLS for path analysis to assess direct and indirect effects. Findings reveal that financial planning significantly enhances both financial literacy and financial resilience, underscoring its pivotal role in promoting financial stability. However, saving behavior shows a non-significant direct impact on financial literacy and a marginally significant effect on financial resilience. Importantly, financial literacy mediates the relationship between financial planning and financial resilience, emphasizing its critical influence on customers' financial resilience. These results highlight the importance of tailored financial education initiatives and strategic planning interventions in enhancing financial literacy and resilience within Islamic banking contexts.